Changes in peak discharge based on sago land use scenarios in the upstream Rongkong watershed, Indonesia - Yumna Yumna; Sugeng Prijono; Wahid Wahid; Srida Mitra Ayu; Witno Witno (Journal of Degraded and Mining Lands Management, 2022)
Land use affects changes in peak discharge so that it has the potential to cause or prevent flooding. Sago has morphological characteristics that have the potential to absorb more water. This study aimed to determine the magnitude of the change in peak discharge in the upstream watershed after sago planting. Observations were made on the three growth phases of sago palms (initial, middle, and mature phases). The research stages included calculating the runoff coefficient value under sago stands at three growth phases. Peak discharge of the existing conditions (settlements, rice fields, mixed gardens, shrubs, sand dunes, forests, and water bodies) was estimated after three scenarios of sago land use. The scenarios consisted of 25% of the land area planted with sago (scenario 1), 50% for scenario 2, and 100% for scenario 3. The data were analyzed quantitatively by comparing peak discharge in the existing conditions with scenario results. The results showed that the peak discharge in the existing conditions was 52.36 m3 hour-1. Peak discharge in the initial phase of scenario 1 was 18.94 m3 hour-1, scenario 2 was 37.88 m3 hour-1, and scenario 3 was 75.77 m3 hour-1. Peak discharge in the middle phase of scenario 1 was 19.01 m3 hour-1, scenario 2 was 38.02 m3 hour-1, and scenario 3 was 76.04 m3 hour-1. Peak discharge in the mature phase of scenario 1 was 6.38 m3 hour, scenario 2 was 12.76 m3 hour-1, and scenario 3 was 26.55 m3 hour-1. The peak discharge in the upstream watershed decreased after the scenarios with the use of sago land for all growth phases, except for scenario 3 of the initial and middle phases.